2018
DOI: 10.7861/clinmedicine.18-2-118
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow Blatchford Score and risk stratifications in acute upper gastrointestinal bleed: can we extend this to 2 for urgent outpatient management?

Abstract: Upper gastrointestinal (GI) bleeds are a common presentation to emergency departments in the UK. The Glasgow Blatchford score (GBS) predicts the outcome of patients at presentation. Current UK and European guidelines recommend outpatient management for a GBS of 0. In the current study, our aim was to assess whether extending the GBS allows for early discharge while maintaining patient safety. We also analysed whether pathologies could be missed by discharging patients too early. Data were retrospectively colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
0
21
1
2
Order By: Relevance
“…In our study, in predicting need for blood transfusion, all scores performed well, but modified AIMS65 had slightly better accuracy; however, in predicting need for endoscopic intervention, only modified AIMS65, GBS and FRS had meaningful accuracy (p < 0.05). Although, outperformance of GBS in assessment of need for clinical intervention has been shown in other studies [20,[24][25][26], we found modified AIMS65 as a good fit alternative.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In our study, in predicting need for blood transfusion, all scores performed well, but modified AIMS65 had slightly better accuracy; however, in predicting need for endoscopic intervention, only modified AIMS65, GBS and FRS had meaningful accuracy (p < 0.05). Although, outperformance of GBS in assessment of need for clinical intervention has been shown in other studies [20,[24][25][26], we found modified AIMS65 as a good fit alternative.…”
Section: Discussioncontrasting
confidence: 57%
“…This cut off was increased to ≤1 in the prospective study conducted by Stanley, J. et al and except one, none of the patients required intervention nor transfusion [27]. This cut off has also been extended safely to ≤2 in some studies [2,24,25]. Increasing the cutoff point acts as two edged sword.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Комментарии ной воспалительной реакции, после чего могут быть применены хирургический и/или эндоскопический методы лечения [10,37,38,42,43]. Важно отметить, что при язвенном кровотечении риск смерти коморбидного пациента прямо коррелирует с количеством сопутствующих заболеваний [44].…”
Section: хирургическое лечениеunclassified
“…3 These offer us evidence to inform the delivery of high-quality care whilst at the same Maintaining optimism in adversity: physicians leading innovation, education and responsible care delivery time relieving pressure on emergency departments and acute admissions units. While much of the pressure on the system in the winter crises has been blamed on sicker patients and naive centralist solutions moving care to the community, we should not discard all attempt to appropriately rationalise inpatient care, in scarce hospital beds, where possible.…”
mentioning
confidence: 99%